2013
DOI: 10.1007/978-3-642-37437-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding In-Game Banner Ad Clicks with Tangible Incentives

Abstract: Abstract. Mobile games in the past years have become a new, growing channel for advertisers to reach their customers. The wide spread use of mobile devices, such as smart phones, tablets and PDAs, facilitates the delivery of a variety of highly targeted interactive advertising messages including the use of mobile games as a media. As the phenomenon is new, the literature on mobile in-game advertising is very scarce. The objective of this research is to bridge this gap by studying the consumers' general attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Prior research has also asserted that satisfaction can be theoretically related to value cocreation (Ranjan and Read, 2016;Nambisan and Baron, 2007). Research has shown that in terms of positive behavioral outcomes such as revisit intentions (Komulainen et al, 2013;Rather et al, 2021), several other favorable effects can be drawn through consumer value co-creation intentions (Chathoth et al, 2016). Therefore, it can be expected that consumers who are co-creating higher value with sharing economy platforms will display an enhanced brand preference and develop sustainable social relationships.…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%
“…Prior research has also asserted that satisfaction can be theoretically related to value cocreation (Ranjan and Read, 2016;Nambisan and Baron, 2007). Research has shown that in terms of positive behavioral outcomes such as revisit intentions (Komulainen et al, 2013;Rather et al, 2021), several other favorable effects can be drawn through consumer value co-creation intentions (Chathoth et al, 2016). Therefore, it can be expected that consumers who are co-creating higher value with sharing economy platforms will display an enhanced brand preference and develop sustainable social relationships.…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%
“…Prior literature has noted that the inclusion of messaging can have a positive impact on the success of a banner ad campaign (Brettel and Spilker-Attig, 2010;Lwin and Phau, 2013;Idemudia and Jones, 2015). Banner ads that include messaging about incentives, such as offers, or specific benefits, such as product features, have been found to be more effective than ads without any messaging (Komulainen et al, 2013). Banner ads with a clear message that communicates value to the user can positively impact the perceived usefulness of the banner ad and subsequently impact attitude toward the ad and intention to click on the ad (Idemudia and Jones, 2015).…”
Section: Theory and Hypothesesmentioning
confidence: 99%